Altered large-scale internetwork functional connectivity in patients with vestibular migraine and migraine without aura. (13th March 2023) - Zhang, Bing; Wu, Dongpeng; Guo, Yonghua; Yan, Wenjing; Liu, Xuejun; Yang, Zhengjie; Deng, Jin; Wang, Haiping
Highlights: We assessed large-scale internetwork functional connectivity in VM and MwoA patients. Functional connectivity between the lFPN and rFPN was reduced in patients with MwoA compared with HCs. VM patients showed decreased functional connectivity between the DAN, SMN, pmVN, and lVN compared to patients with MwoA. Abstract: Objective: To investigate large-scale internetwork functional connectivity in patients with vestibular migraine (VM) and migraine without aura (MwoA). Methods: Resting-state functional magnetic resonance imaging data from 34 VM patients, 34 MwoA patients, and 33 healthy controls (HCs) were collected and the results were analyzed using independent component analysis (ICA). We also analyzed the correlations between clinical data and internetwork functional connectivity. Results: In contrast to HCs, MwoA patients showed decreased functional connectivity between the left frontoparietal network (lFPN) and right frontoparietal network (rFPN), with increased functional connectivity between the sensorimotor network (SMN) and lateral visual network (lVN). When compared to MwoA patients, VM patients demonstrated decreased functional network connectivity between the dorsal attention network (DAN) and posterior medial visual network (pmVN), between the SMN and pmVN, and between the SMN and lVN. Meanwhile, increased functional network connectivity was found between the lFPN and rFPN; however, there was no significant difference in functional network connectivity between VM patients and HCs. In addition, associations were found between clinical data and internetwork functional connectivity. Conclusion: Functional connectivity between the lFPN and rFPN was reduced in patients with MwoA compared with HCs, which may indicate functional impairment in cognitive control, attention, somatosensory perception, and emotion regulation in patients with MwoA. VM patients showed decreased functional connectivity between the DAN, SMN, pmVN and lVN compared to patients with MwoA, which could account for the multisensory integration abnormalities and be the cause of vestibular symptoms in VM patients. These findings offer fresh perspectives on the pathophysiology of VM and MwoA.